Analisis Kompetensi Pedagogik Guru PAI Dalam Kegiatan Pembelajaran PAI di SMA Bakong Pittaya School Pattani Thailand - Fitriyani Fitriyani; Maryono Maryono; Muhtar Sofwan Hidayat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
A keyelement in the growth of teaching as a professionis teacher competency. A teacher needs to be proficient in a variety of behaviors, knowledge, and abilities in order to accomplish their professional tasks, which are demonstrated in their performance. When it comes to designing learning activities that will provide the best learning out comes, pedagogical expertise is the most important factor to take in to account. In actuality, though, there are still educators who lack pedagogical competency. The purpose of this study is to evaluate the Islamic Education (PAI) teachers' pedagogical proficiency in PAI learning activities at Bakong PittayaSchool in Pattani, Thailand. To comprehend the elements influencing the level of pedagogical competenceof PAI instructors at Bakong Pittaya School in Pattani, Thailand, as well as the characteristics of teacher competence in Thailand. This study takes a descriptive approach while using a qualitative research methodology. Data collection techniques, content analysis, interviews, and observation are all part of qualitative research. This study is being conducted at Bakong Pittaya School in Pattani, Thailand. According to the author's discussions with Islamic Education instructors and the school director, the pedagogical ability of PAI teachers at Bakong Pittaya School in Pattani, Thailand, is deemed good. Three components make up the pedagogical competency of PAI teachers: creating learning implementation plans (RPPs), carrying out learning, and conducting assessments. Teacher competency in Thailand is regulated by a teacher constitution that out lines the abilities or competencies a teacher must have, referred to as the teacher standards. Factors affecting the quality of pedagogical competence of PAI teachers in Thailand include internal factors such as efforts and initiatives from the PAI teachers themselves to develop knowledge in their field. Lack of discipline and responsibility among teachers pose a significant challenge for schools in Thailand in improving teacher competence. External factors include the school's support in providing learning facilities. Supporting factors involveactive participation from parents, community associations, teacher representatives, student representatives, directors, and principals, as well as academic experts/advisors, all of whom are part of the school committee. Keywords: , ,